Characteristics of AlN inclusions in low carbon Fe–Mn–Si–Al TWIP steel produced by AOD-ESR method. (15th March 2016) - Liu, H.; Liu, J.; Michelic, S.; Wei, F.; Zhuang, C.; Han, Z.; Li, S.
Abstract : Argon oxygen decarburisation–electroslag remelting (AOD-ESR) process has been well used to produce the Fe–Mn–Si–Al twinning induced plasticity steel (TWIP) steels. The characteristics of AlN inclusions formed in TWIP steels after AOD refining, ESR and forging process were investigated by scanning electron microscopy and X-ray energy dispersive spectrometry. An automated program called 'INCAFeature' was used to collect statistics of inclusion characteristics. Great differences on the amount, distribution and morphologies of AlN inclusions were observed in AOD ingots, ESR ingots and forgings. The dominating inclusions in AOD ingots are mainly single Al(O)N and MnS(Se)–Al(O)N aggregate, accounting for 66.7% of the total inclusions. After the ESR process, AlN inclusions in all size range significantly decreased, which were rarely observed in ESR ingots. Thermodynamic calculations show that AlN inclusions can precipitate in the liquid Fe–Mn–Si–Al TWIP steels, which is different from the viewpoint of literatures that the precipitation of AlN inclusions took place at solidifying front or solid phase. Furthermore, the thermodynamic calculation result has been verified by high temperature laser scanning confocal microscope experiments.